A critical account of the concept of 'basic legal knowledge': theory and practice - Ordóñez-López, Pilar (The interpreter and translator trainer, 2015)
Subject knowledge is, according to most definitions, one of the basic components of legal translation competence. There is widespread agreement that legal translators must have some basic knowledge of the legal systems involved in order to perform satisfactorily. Nevertheless, no concrete proposals have been put forward and no real consensus can be observed with regard to the elements which should be covered by the notion of 'basic legal knowledge'. In this study, a critical account of this concept is provided through the examination of the undergraduate modules on legal translation taught at Spanish universities, focusing on the legal topics covered as well as the materials included in these modules. The aim of this review is to shed some light on how this concept is incorporated into the teaching of legal translation, in order to identify, by means of a bottom-up approach, which components are considered most central to the blanket notion of 'basic legal knowledge'.